Glucose lowering and pancreato-protective effects of Abrus Precatorius (L.) leaf extract in normoglycemic and STZ/Nicotinamide – Induced diabetic rats. (10th August 2020) - Boye, Alex; Acheampong, Desmond Omane; Gyamerah, Eric Ofori; Asiamah, Ernest Amponsah; Addo, Justice Kwaku; Mensah, Derrick Addae; Brah, Augustine Suurinobah; Ayiku, Philippa Jennifer
Abstract: Ethnopharmacological relevance: Abrus precatorius (L.) leaves are used as folk medicine by the local communities in the western region of Ghana to treat diabetes mellitus; however, this health claim remains unverified scientifically. Objective: The study investigated glucose lowering and pancreato-protective effects of Abrus precatorius leaf extract (APLE) in normoglycemic and STZ/nicotinamide (NIC)-induced diabetic rats. Method: after preparation of APLE, it was subjected to phytochemical screening, proximate composition and elemental assessments by using standard methods. Oral glucose tolerance test (OGTT) and maltose, lactose and sucrose oral challenge were assessed in normoglycemic rats post-APLE. Morphological characteristics of glucose response curve (time of glucose peak and shape of glucose response curve) were determined. Subsequently, diabetes mellitus was experimentally established in normoglycaemic adult Sprague-Dawley rats (weighing 150–250 g) of both sexes by sequential injection of Streptozotocin (STZ, 60 mg/kg ip )-reconstituted in sodium citrate buffer and NIC (110 mg/kg ip )-reconstituted in normal saline (1:1 v/v) for 16 weeks. Except control rats (normal saline 5 ml/kg ip; baseline fasting blood glucose [FBG] of 6.48 mmol/L), rats having FBG (stable at 11.1 mmol/L or ≥ 250 mg/dL) 3 days post-STZ/NIC injection were randomly re-assigned to one of the following groups: model (STZ/NIC-induced diabetic rats), APLE (100, 200 and 400 mg/kg respectively po ) and metformin (300 mg/kg po ) and treated daily for 28 days. Bodyweight and FBG were measured on weekly basis. FBG was measured by using standard glucometers. On day 28, rats were sacrificed under chloroform anesthesia, blood collected via cardiac puncture; kidney, liver and pancreas surgically harvested. While the pancreas was processed, sectioned and H&E-stained for histological examination, fresh kidney and liver were homogenized for assessment of total anti-oxidant capacity. Median cross-sectional area of pancreatic islets of Langerhans was determined for each group by using Amscope. Results: Cumulatively, APLE (100, 200 and 400 mg/kg respectively) dose-dependently decreased the initial FBG by 55.22, 76.15 and 77.77% respectively compared to model (−1.04%) and metformin (72.29%) groups. APLE treatment recovered damaged pancreatic β-cells and also increased median cross-sectional area (x10 6 μm 2 ) of pancreatic islets compared to that of model group. APLE significantly (P < 0.05) increased total anti-oxidant capacity (5.21 ± 0.02 AscAE μg/mL) of plasma, kidney and liver compared to model (4.06 ± 0.04 AscAE μg/mL) and metformin (4.87 ± 0.03 AscAE μg/mL) groups. Conclusion: APLE has demonstrated glucose lowering and pancreato-protective effects in rats and arrested the characteristic loss in bodyweight associated with diabetes mellitus. This finding preliminarily confirms folk use of APLE as an anti-diabetic herbal medicine, whiles providing a rationale for further translational studies on APLE. Graphical abstract: Image 1